Production of forage peanut hybrids through artificial hybridization - Oliveira, Marilda Augusta Peres; Valls, José Francisco Montenegro (Pesquisa Agropecuaria Brasileira, 2002)
The purpose of this work was to obtain forage peanut hybrids through artificial hybridization. The experiment was conducted in a screenhouse at Embrapa-Centro Nacional de Pesquisa de Recursos Genéticos e Biotecnologia during the flowering period of Arachis pintoi Krap. & W. C. Gregory and A. repens Handro accessions. About 700 pollinations produced 27 fruit segments and the fertilization rates ranged from 1.1 to 12.9% for all cross combinations. The intraspecific hybrids produced F2 seeds, which did not occur to the interspecific hybrids. To effect the hybridization technique, adjustments were necessary to forage Arachis species, in relation to cultivated peanut, since differences in the growth habit were verified.